Do countries with stronger family ties experience lower level of financial development? - Lim, Jodyn Zhen Ting (2018)
This paper examines the effect of strength of family ties on the level of financial development across 80 countries using OLS and IV-2SLS frameworks. We amalgamate two emerging strands of literature, the sources of financial development and the effect that family ties have on economic behaviour. To mitigate endogeneity bias, we adopt a novel instrument, wheat suitability ratio, to proxy family ties. Our results reveal that the strength of family ties is significantly and negatively correlated with financial development. Our OLS and IV estimates indicate that a one standard deviation increase in strength of family ties leads to a 37.3% and 24.3% decrease in main financial outcome variable, account respectively.